Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Impact Report 2019-2020 - 4Korners (2020)

Rapport d'impact 2019-2020 - 4Korners (2020)